Multiple Closed Loop System Control with Digital PID Controller Using FPGA - Akkaya, Sirin; Akbati, Onur; Gorgun, Haluk (IEEE, 2014)
PID (roportional - Integral - Derivative) controllers are the most widely used closed loop controllers due to their simplicity, robustness, effectiveness and applicability for much kind of systems. With the rapid development of technology, implementation of PID controller has gone several steps from using analog components in hardware to using some software-based program to execute PID instructions digitally in some processor-based systems. And also, these developments have brought an alternative solution to implement PID instructions in Programmable Logic Devices (PLD). Field Programmable Logic Array (FPGA) is the most advanced members of PLDs. This paper presents the digital PID algorithm on FPGA. The controller algorithm is developed using VHDL and implemented using Altera DE0 Nano Board. As the controlled system, five axis robot arm is selected, which have five dc motor and four potentiometer to determine the positions of motors. The results show that digital PID controller and also multi-feedback control systems can be implemented successively using FPGA devices.
Keywords: fpga; digital pid; pwm; vhdl; robot arm; Automation & Control Systems; Computer Science; Engineering